Factors Affecting Sustainability of Microfinance Institutions in Nepal - Dhungana, Bharat Ram; Khanal, Sujata; Pokhrel , Om Prakash; Dhakal, Bishnu Prasad (Kshitiz Management Review, 2026)
The sustainability of MFIs is a crucial issue for the maximalist perspective of microfinance. Most of the MFIs deviated from the social mission and created several issues in the field of microfinance. This study aims to examine the factors affecting the sustainability of MFIs in Nepal. A quantitative research approach was adopted with the survey confined to 37 branches of MFIs working in three municipalities - Shuklagandaki, Bhimad, and Vyas of Tanahun district. Each branch has six employees on average and the total population for this study is 222 employees. The survey was administered to the entire population. However, 179 complete responses were received using structured questionnaires. The study finds financial (financial self-sufficiency, profitability), operational (operational efficiency and risk management), social (outreach and client retention and satisfaction), environmental (regulatory environment, macroeconomic condition), and competitive factors are positively correlated to microfinance sustainability. Social, environmental, and competitive factors are the most important factors that affect the sustainability of microfinance institutions in Nepal. The findings of this research have important policy implications to increase the sustainability of MFI in Nepal. Policymakers may focus on strengthening the regulatory structure, improving operational and financial self-sufficiency and promoting social outreach to unbanked people.